Hubungan Penyuluhan dalam Program Rehabilitasi Sosial dengan Perubahan Perilaku Anak Jalanan di Kota Cimahi - Yachsa Baihaqi; Mochammad Rochim (Bandung Conference Series: Communication Management, 2023)
Abstract. The phenomenon of social welfare problems in Indonesia is no longer a foreign thing, in every area, both cities and districts, it must have people with social welfare problems as happened in Cimahi City. There are not a few people with social welfare problems, especially the number of children with social welfare problems is also quite large. Seeing the phenomenon of welfare problems in Cimahi City, the institution that has the main task of formulating and managing operational policies in the field of Social Welfare in Cimahi City is the Social Service. The Cimahi City Social Service has a Social Rehabilitation program to address persons with social welfare issues. One of the success factors of counseling in social rehabilitation programs is the need for communicators, media, and messages to be conveyed. Therefore, this study aims to determine the relationship between counseling in social rehabilitation programs and changes in the behavior of street children in Cimahi City, the counseling includes communicators, media, and messages conveyed. This research uses stimulus-response theory. This S-R theory gives an understanding of the influence on the receiving party as a result of an interaction. In summary, this theory explains the influence that stimuli have. This research uses correlational methods and quantitative approaches. Data collection techniques were carried out with questionnaires and literature studies. The sample in this study was 48 respondents who were children who were recorded in coaching activities carried out by the Cimahi City Social Service. The data analysis techniques used are descriptive analysis and correlation testing using IBM SPSS Statistics for Windows. The result of this study is that there is a relationship between counseling in social rehabilitation programs and changes in the behavior of street children in Cimahi City in a high relationship category, meaning that changes in the behavior of street children in Cimahi City are influenced by counseling in social rehabilitation programs carried out by the Cimahi City Social Service. Abstrak. Fenomena masalah kesejahteraan sosial di Indonesia bukan lagi hal yang asing terdengar, disetiap daerah baik kota maupun kabupaten pasti memiliki penyandang masalah kesejahteraan sosial seperti yang terjadi di Kota Cimahi. Penyandang masalah kesejahteraan sosial tidak sedikit, apalagi angka anak penyandang masalah kesejahteraan sosial juga cukup banyak. Melihat fenomena masalah kesejahteraan di Kota Cimahi, lembaga yang memiliki tugas pokok untuk merumuskan dan mengurusi kebijakan operasional di bidang Kesejahteraan Sosial di Kota Cimahi yaitu Dinas Sosial. Dinas Sosial Kota Cimahi memiliki program Rehabilitasi Sosial untuk mengatasi penyandang masalah kesejahteraan sosial. Salah satu faktor keberhasilan penyuluhan dalam program rehabilitasi sosial yaitu perlu adanya komunikator, media, dan pesan yang disampaikan. Oleh karena itu penelitian ini bertujuan untuk mengetahui hubungan penyuluhan dalam program rehabilitasi sosial dengan perubahan perilaku anak jalanan di Kota Cimahi, penyuluhan tersebut meliputi komunikator, media, dan pesan yang disampaikan. Penelitian ini menggunakan teori Stimulus-Respon. Teori S-R ini memberi pemahaman mengenai pengaruh pada pihak penerima akibat dari sebuah interaksi. Secara ringkasnya teori ini menjelaskan keberpengaruhan yang ditimbulkan oleh rangasangan. Penelitian ini menggunakan metode korelasional dan pendekatan kuantitatif. Teknik pengumpulan data dilakukan dengan kuesioner dan studi kepustakaan. Sampel pada penelitian ini sebanyak 48 responden yang merupakan anak yang terdata dalam kegiatan pembinaan yang dilakukan oleh Dinas Sosial Kota Cimahi. Teknik analisis data yang digunakan yaitu analisis deskriptif dan uji korelasi menggunakan IBM SPSS Statistic untuk Windows. Hasil dari penelitian ini adalah terdapat hubungan antara penyuluhan dalam program rehabilitasi sosial dengan perubahan perilaku anak jalanan di Kota Cimahi dalam kategori hubungan yang tinggi, artinya bahwa perubahan perilaku anak jalanan di Kota Cimahi dipengaruhi oleh penyuluhan dalam program rehabilitasi sosial yang dilakukan oleh Dinas Sosial Kota Cimahi.